Representations of Magical Realism in the Works of Afifa Laibi and Fernando Botero (A Comparative Study) (Al-Academy, 2025)
This research dealt with the study of representations of magical realism in the works of the artist Afifa Laibi and Fernando Botero. The study came in four chapters. The first chapter represents the general framework of the research and includes the research problem that represented the way to answer the questions raised by the researcher, including: How was magical realism represented in the works of the artist Afifa Laibi and Fernando Botero? The importance of the research also lies in defining the magical realism approach in the field of art. As for the goal of this study, it was represented in revealing the representations of magical realism in the works of the artist Afifa Laibi and Fernando Botero. The theoretical framework included two topics: the first: the concept of magical realism in the field of art, and the second was represented by two topics: the first is Fernando Botero, the experience and style, while the second topic is Afifa Laibi, the experience and style. As well as analyzing samples of two samples for the artists, and after the analysis process, the researcher reviewed the results, including For conclusions, recommendations and source list.